Síntese e caracterização de nanopartículas de TiO2 pelo método do precursor polimérico - Zoccal, João Victor Marques (Universidade Federal de São Carlos, 2010)
Currently, scientific research in the field of nanotechnology has attracted growing interest because of its several applications, either through design of new products, materials characterization, production and application of structures, devices and systems in the form or function are features of the nanoscale. Thus, there is advancement in technology and industrial application involving nanoparticles, however, raise the concern with control of nanoparticles released into the environment, which is one of the most harmful to human health by causing an increase in the incidence cardio-respiratory disease. Several techniques for production of nanoparticles, and methods of chemical synthesis, have been developed and improved. Among the various methods of chemical synthesis used in the preparation of nanoparticles of titanium dioxide (TiO2), the polymeric precursor method, also called Pechini method, has stood successfully for the issue of nanomaterial. In this context, this work aims to generate in the laboratory a nano material alternative that can be dispersed in a gas stream, forming an aerosol in motion. Furthermore, it should be synthesized in sufficient quantities to use as the test aerosol relatively simple and inexpensive. The technique is primarily on the reaction between citric acid with titanium isopropoxide, obtaining as a product of titanium citrate. After the synthesis of citrate, the addition of ethylene glycol polymerization promoted by a reaction polyesterification, resulting in a polymeric resin clear and viscous. At the end of the process, the resin is burned to remove organic matter and oxidation of the metal cation, forming nanoparticles of TiO2. The powders were characterized by several techniques, among them the thermal analysis, absorption spectroscopy in the infrared, X-ray diffraction (XRD), Raman spectroscopy, UV Visible spectroscopy, method of nitrogen / helium adsorption (method BET), and the Particle Scanning Mobility Sizer (SMPS), which examined the dispersion of the size of nanoparticles as a function of concentration in the gas stream. The results obtained in the characterization techniques showed that the polymeric precursor method was promising in obtaining nano-TiO2. In addition, the SMPS can be observed a high concentration of TiO2 nanoparticles in the range of 15 to 50 nm.
Keywords: Engenharia química; Partículas nanométricas; Dióxido de titânio; Método de Pechini; SMPS; Método do precursor polimérico; Nanoparticles; Titanium dioxide; Polymeric precursor method; ENGENHARIAS::ENGENHARIA QUIMICA